OPTIMALISASI INSPEKTORAT KABUPATEN BANYUMAS DALAM MELAKUKAN PENCEGAHAN TINDAK PIDANA KORUPSI - tiara dwihanasetia (MIH Unsoed, 2022)
The crime of corruption is called an extraordinary crime (extra ordinary crime) which can damage the entire system of life, even to the moral and mental damage of the community, as well as harm the state. In fact, there are still abuses of power by government officials in the form of providing facilities and preferential treatment to other parties aimed at benefiting themselves. Acts of corruption are mark ups, budget abuse, embezzlement, fictitious reports, bribery, fictitious activities/projects, illegal levies, abuse of authority, circumcision/cutting, gratuities, extortion, double budgeting and mark downs. It is necessary to optimize the role of the Regency/Municipal Inspectorate as a supervisor for the implementation of a clean and free regional government from corruption, collusion and nepotism. As regulated by Law Number 20 of 2001 concerning Eradication of Criminal Acts of Corruption; Permendagri No. 23 of 2007 concerning Guidelines for Supervision of Regional Government Administration; Law (UU) Number 23 of 2014 concerning Regional Government. The aims of this study are (1) to explain and analyze the optimization of the Banyumas Regency Inspectorate in supervising and preventing corruption; (2) to explain and analyze the obstacles of the Banyumas Regency Inspectorate in carrying out its role in supervising and preventing corruption. The use of descriptive qualitative research methods normative juridical approach in this study obtained two conclusions, namely (1) the role of the Regional Inspectorate of Banyumas Regency in supervising and preventing corruption has been optimally proven by awards for the management of gratuities from the results of achieving local government performance based on the best accountability system in Indonesia. -Central Java. The decreasing number of problematic OPD or ASN every year and all OPD or ASN carry out their duties and responsibilities well. (2) The obstacle for the Banyumas Regency inspectorate in carrying out its role is the limited budget for increasing APIP HR, the number of APIP available is not sufficient for the needs.